Pengaruh Kompos Kulit Tanduk Kopi dalam Peningkatan Kualitas Media Tanam Pembibitan Alpukat (Persea Americana Miller) di Persemaian Permanen Marinding Kabupaten Tana Toraja - Pali’ Padang, Wesni; Irmayanti Idris, Andi; Rusmidin (Pangale Journal of Forestry and Environment, 2024)
Coffee Coffee horn husk, as an organic waste, has the potential to improve soil fertility by adding nutrients and improving soil physical structure. The purpose of this study was to analyze the impact of applying compost fertilizer from coffee horn skin with different treatments, using the analysis of variance method in a Randomized Group Design (RAK). The samples in this study were avocado plants (Persea Americana Miller) with the following treatments: P0 without compost, P1 using 300 grams of coffee horn skin compost, P2 using 400 grams of coffee horn skin compost, and P3 using 500 grams of coffee horn skin compost. In addition, the groups of seeds used consisted of large seeds (weighing 60-67 grams), medium seeds (weighing 40-47 grams), and small seeds (weighing 20-28 grams). The results showed that the best dose of coffee horn skin compost to support the growth of avocado plant height, stem diameter, and number of leaves (strands) of avocado was 500 grams. The most effective group to use is the large seed group